Data Integration in the Life Sciences 9th International Conference, DILS 2013, Montreal, QC, Canada, July 11-12, 2013. Proceedings - Baker, Christopher J. O.; Butler, Greg.; Jurisica, Igor.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 9th International Conference on Data Integration in the Life Sciences, DILS 2013, held in Montreal, QC, Canada, in July 2013. The 10 revised papers included in this volume were carefully reviewed and selected from 23 submissions. The papers cover a range of important topics such as algorithms for ontology matching, interoperable frameworks for text mining using semantic web services, pipelines for genome-wide functional annotation, automation of pipelines providing data discovery and access to distributed resources, knowledge-driven querying-answer systems, prizms, nanopublications, electronic health records and linked data.
Algorithms for ontology matching -- Interoperable frameworks for text mining using semantic web services -- Pipelines for genome-wide functional annotation -- Automation of pipelines providing data discovery and access to distributed resources -- Knowledge-driven querying-answer systems -- Prizms -- Nanopublications -- Electronic health records -- Linked data.
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Computer Communication Networks; Database Management; Data Mining and Knowledge Discovery